BUILDING STUDENTS' UNDERSTANDING OF QUADRATIC EQUATION CONCEPT USING NAÃVE GEOMETRY - Fachrudin, Achmad Dhany; Ilma, Ratu; Darmawijoyo, Darmawijoyo (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
The purpose of this research is to know how Naive Geometry method can support students' understanding about the concept of solving quadratic equations. In this article we will discussÃ‚Â one activities of the four activities we developed. This activity focused on how students linking the Naive Geometry method with the solving of the quadratic equation especially on how student bring geometric solution into algebraic form. This research was conducted in SMPÃ‚Â Negeri 1 Palembang. Design research was chosen as method used in this research that have three main phases. The results of this research showed that manipulating and reshaping theÃ‚Â rectangle into square could stimulate students to acquire the idea of solving quadratic equations using completing perfect square method. In the end of the meeting, students are also guided to reinvent the general formula to solve quadratic equations.Keywords: Quadratic Equations, Design Research, Naive Geometry, PMRI